DECREASED SERUM VITRONECTIN LEVEL IN SYSTEMIC SCLEROSIS - Gundogdu, B.; Yolbas, S.; Yildirim, A.; Aydin, S.; Koca, S. S. (Bmj Publishing Group, 2014)
[Abstract Not Available]
15th Annual European Congress of Rheumatology (EULAR) -- JUN 11-14, 2014 -- Paris, FRANCE